ADMET study, spectroscopic characterization and effect of synthetic nitro chalcone in combination with norfloxacin, ciprofloxacin, and ethidium bromide against Staphylococcus aureus efflux pumps. (16th September 2022) - Rocha, Janaína E.; de Freitas, Thiago S.; Xavier, Jayze C.; Pereira, Raimundo L. S.; Pereira Junior, Francisco N.; Nogueira, Carlos E. S.; Marinho, Márcia M.; Bandeira, Paulo N.; Rodrigues, Leilane G.; Marinho, Emmanuel S.; de Lacerda, Bruna C. G. V.; de Andrade, Edlane Martins; et al.
Abstract: Chalcones are present in a wide variety of plants, having in their structure two aromatic rings that are linked together by a chain composed of three carbon atoms with α, β‐unsaturated to carbonyl system. Bacteria have several drug resistance mechanisms, among them the efflux pump; this mechanism, when active, is able to expel different compounds from inside bacterial cells. Several efflux pumps have already been identified for Staphylococcus aureus bacteria, including MepA and NorA. Many chalcones have been isolated and identified with various activities, such as antimicrobial. In view of this, this article aimed to evaluate the antibiotic modifying effect of chalcone (E)‐1‐(2‐hydroxyphenyl)‐3‐(3‐nitrophenyl)prop‐2‐en‐1‐one against S. aureus carrier of NorA and MepA efflux pump. Regarding the antibiotic, there was a synergism when associated with ciprofloxacin in SA‐K2068 strain, showing this chalcone as an alternative to reverse the resistance to this medicine. The physicochemical properties calculated were fundamental in the description of the predicted pharmacokinetic properties. Despite the mutagenic risk caused by the metabolic activation of nitrochalcone, it is possible to notice a pharmacological principle in a longer half‐life for the performance of biological activities. The compound has a good bioavailability, as it is highly absorbed in the intestine and easily transported by plasma proteins, in addition to not presenting neurotoxic, hepatotoxic, and cardiotoxic damage.